Association of Diabetes Mellitus and Hypertension with Angiographic Profile of Acute Coronary Syndrome Patients - Salik Ahmed, Uzair Abbas, Sanam Khowaja, Shahbaz Ali Shah, Muhammad Hashim, Amjad Ali Hulio (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cardiovascular diseases are the leading cause of death worldwide while ischemic heart disease is a major contributor of cardiovascular diseases and diabetes mellitus is one of the major risk factor for ischemic heart diseases. Cardiac involvement in diabetes commonly manifest as coronary artery disease (CAD) of different extent which has an impact on disease outcome and prognosis. Aim: To compare the angiographic profiles between diabetic and non-diabetic patients with acute coronary syndrome (ACS). Place and duration of study: National Institute of Cardiovascular Diseases, Karachi, Pakistan from 1st Feb. 2020 to 31st Jan. 2021. Methodology: Two hundred and ninety eighty patients with acute coronary syndrome were enrolled. Demographic profile, personal and family history was taken through questioner. Angiography was performed to assess the angiographic profile in terms of extent of the disease, left main disease (LMD) involvement, severity of disease, and localization of disease to see the association with variables. Results: The mean age was 56.38±8.90 years and 240 (81%) were males and 58 (19%) were females. The diabetic patients have higher frequency of three vessels involved, localization of left anterior descending (LAD) and right coronary artery (RCA) with significant difference (p<0.0001 respectively). Left main disease was noted in 21 (25.3%) of diabetic participants and severe disease was found among 119 (56.4%) of diabetic participants with significant difference compared to non-diabetics (p<0.001). Angiographic profile was also found to be significantly different among hypertensive and non-hypertensive participants (p<0.05) Conclusion: There is higher frequency of diabetes in patients with ACS and most of them are male. While severity of disease, involvement of RCA and LAD in patients with acute coronary syndrome is quite high in patients with diabetes mellitus as compared to non-diabetic patients. Hypertension was also found to be associated with angiographic profile.